Concordance of Intradepartmental Consultations of Barrett's Dysplasia. (11th September 2019) - Chen, Fengming; Liu, Yongjun; Ruggiero, Francesca
Abstract: Introduction: Barrett's esophagus (BE) is a well-known precursor to esophageal adenocarcinoma (EAC). Simple BE has an annual rate of progression to EAC of only up to 0.5%, while BE with low-grade dysplasia (LGD) or with high-grade dysplasia (HGD) has a higher progression rate of 10% and 40%, respectively. Therefore, accurate diagnosis and grading of dysplasia in BE are critical for optimal patient management. However, grading dysplasia is not well defined in practice, which often results in poor interobserver and/or intraobserver reproducibility. In this study, we aim to (1) investigate the concordance of intradepartmental consultations of BE dysplasia and (2) compare consultant diagnosis with final diagnosis and follow-up diagnosis. Methods: We retrospectively reviewed 856 intradepartmental consultation records obtained from May 2017 to March 2018. For cases of Barrett's dysplasia in biopsy specimens, H&E-stained slides were re-reviewed and the corresponding clinical information was retrieved from the electronic medical record. Results: Twenty intradepartmental consultation cases of Barrett's dysplasia were identified (involving 2 females and 18 males, mean age 67.8 ± 8.6 years, ranging 50-81 years). The most frequent reasons for consultation were indefinite dysplasia (IND) vs LGD and LGD vs HGD. Half of the cases showed concordance between referring pathologist and consultant pathologist(s), while 10% of the case showed a major discrepancy (resulting in significant changes in patient management and/or prognosis) and 40% showed a minor discrepancy (resulting in no significant impact on patient management and/or prognosis). The final diagnoses were changed after consultation for cases with major discrepancy, while 60% of cases with minor discrepancy remained the original diagnoses. Conclusions: Intradepartmental consultations are strongly recommended for the challenging cases of BE dysplasia, which can effectively prevent over- or underdiagnosis. For challenging cases such as IND vs LGD, two or more consultants are usually needed to reach an agreement.